In Vitro Insulin Resistance Model: A Recent Update. (18th January 2023) - Yudhani, Ratih D.; Sari, Yulia; Nugrahaningsih, Dwi A. A.; Sholikhah, Eti N.; Rochmanti, Maftuchah; Purba, Abdul K. R.; Khotimah, Husnul; Nugrahenny, Dian; Mustofa, Mustofa
Abstract : Insulin resistance, which affects insulin-sensitive tissues, including adipose tissues, skeletal muscle, and the liver, is the central pathophysiological mechanism underlying type 2 diabetes progression. Decreased glucose uptake in insulin-sensitive tissues disrupts insulin signaling pathways, particularly the PI3K/Akt pathway. An in vitro model is appropriate for studying the cellular and molecular mechanisms underlying insulin resistance because it is easy to maintain and the results can be easily reproduced. The application of cell-based models for exploring the pathogenesis of diabetes and insulin resistance as well as for developing drugs for these conditions is well known. However, a comprehensive review of in vitro insulin resistance models is lacking. Therefore, this review was conducted to provide a comprehensive overview and summary of the latest in vitro insulin resistance models, particularly 3T3-L1 (preadipocyte), C2C12 (skeletal muscle), and HepG2 (liver) cell lines induced with palmitic acid, high glucose, or chronic exposure to insulin.